The Effect of sheep serum and estrus sheep serum on in vitro maturation and fertility rate of ewe oocyte - J Wattimena; M Veerman (Indonesian Center for Animal Research and Development (ICARD), 2005)
The main objective of this research was to obtain the effect of sheep serum (SS) and estrus sheep serum (ESS) on in vitro maturation oocyte and ovine fertilization. This study was carried out in experimental laboratory in animal reproduction laboratory, Faculty of Animal Husbandry, Padjadjaran University. Results showed that treatments significantly (P<0,05) influenced on maturation rate for germinal vesicle (GV), germinal vesicle breakdown (GVBD), metaphase-I (M-I) and metaphase-II (M-II), but no significantly (P>0.05) results observed on ovine in vitro fertilization (1, 2 and >2 pronuclei). Concentration of 10-20% ESS in CR1aa media were significantly (P<0,05) better than that of SS on maturation rate of ovine oocyte. Key Words: Sheep Serum, Estrus Sheep Serum, Maturation, Fertilization